The adjudication of miracles: Rethinking the criteria of historicity - Licona, Michael R. (HTS teologiese studies, 2009)
This is the second article in a series of two that discusses whether historians are within their professional rights to investigate miracle claims. In the first, I made a positive case that they are and then proceeded to examine two major arguments in support of a negative verdict to the issue: the principle of analogy and antecedent probability. I argued that neither should deter historians from issuing a positive verdict on miracle claims when certain criteria are met and the event is the best explanation of the relevant historical bedrock. In this second article, I examine three additional objections commonly appealed to by biblical scholars: the theological objection, lack of consensus and miracle claims in multiple religions. The resurrection of Jesus is occasionally cited as an example.